Perceptual abnormalities in an ultra‐high risk for psychosis population relationship to trauma and co‐morbid disorder. Issue 2 (9th August 2017) - O' Connor, Karen; Nelson, Barnaby; Cannon, Mary; Yung, Alison; Thompson, Andrew
Abstract : Aims: The aims of this study were 3‐fold. We wished to investigate whether at baseline entry to an ultra‐high risk (UHR) clinic whether: (1) perceptual abnormalities are more prevalent in those young people with co‐morbid psychiatric diagnoses, (2) perceptual abnormalities are more prevalent in those young people with histories of childhood adversity (childhood trauma, bullying) and (3) perceptual abnormality type is associated with co‐morbid psychiatric diagnoses or histories of childhood adversity. Methods: In a sample of 118 UHR patients we investigated the relationship between perceptual abnormalities and non‐psychotic diagnoses and adverse life events at entry to a UHR clinic. Results: Depressive disorder at baseline was associated with increased odds of experiencing perceptual abnormalities (OR 3.59, P = .004), particularly visual perceptual abnormalities (OR 2.36, P = .02). Borderline personality disorder at baseline was associated with increased odds of any auditory perceptual abnormalities (OR 3.44, P = .04) and specifically second person perceptual abnormalities (OR 2.69, P = .04). A history of childhood trauma and childhood bullying were both associated with increased odds of experiencing perceptual abnormalities at baseline (trauma OR 6.30, P < .001; bullying OR 5.00, P = .01). Conclusions: Our findings suggest that in the UHR population, certain types of perceptual abnormalities index risk for co‐morbid non‐psychotic disorder and indicate prior experience of childhood trauma. The use of detailed phenomenology of psychotic symptoms can help to shape our understanding of risk in UHR patients.